A novel tool against multiresistant bacterial pathogens: lipopeptide modification of the natural antimicrobial peptide ranalexin for enhanced antimicrobial activity and improved pharmacokinetics - Domhan, Cornelius; Uhl, Philipp; Meinhardt, Anna; Zimmermann, Stefan; Kleist, Christian; Lindner, Thomas; Leotta, Karin; Mier, Walter; Wink, Michael (International journal of antimicrobial agents, 2018)
As evolutionarily optimised defence compounds, antimicrobial peptides (AMPs) represent a powerful tool against bacterial infections. Ranalexin, an AMP found in the skin of the American bullfrog (Rana catesbeiana), is primarily active against Gram-positive bacteria, with minimum inhibitory concentrations (MICs) of 8-16 mg/L, but shows weaker activity against Gram-negative bacteria (MICs > 64 mg/L). By substitution of six N-terminal amino acids by saturated fatty acids [decanoic acid (C10:0) to myristic acid (C14:0)], lipopeptide derivatives with enhanced antimicrobial activity were developed. The antimicrobial capacity of the peptides was tested against different bacterial strains, including multiresistant clinical isolates. C13C3lexin, the most potent derivative, showed MICs of 2-8 mg/L against Gram-positive bacteria and 2-16 mg/L against Gram-negative bacteria. In time-kill studies, it was clearly shown that ranalexin and the lipopeptide C13C3lexin function as concentration-dependent, fast-acting substances against different bacteria. Cell viability assays revealed that cytotoxicity towards human cells increases with the chain length of the attached fatty acid (IC50, 12.74-108.10 µg/mL). Furthermore, using positron emission tomography (PET) imaging, pharmacokinetic studies of 68Ga-labelled ranalexin and its derivatives were performed for the first time. Here it was demonstrated that ranalexin is rapidly cleared via the kidneys within 1 h post-injection. In contrast, the lipopeptide showed greatly extended circulation in the bloodstream and a shift from renal to hepatic accumulation characteristics. Therefore, the more favourable pharmacokinetics and enhanced antimicrobial activity clearly demonstrate the potential of the lipopeptide AMPs as novel ammunition against emerging multiresistant bacterial pathogens.
Gesehen am 26.04.2019
Received 16 November 2017